Effect of HMM glutenin subunits on wheat quality attributes - Horvat, Tomica; Kurtanjek, Želimir; Drezner, Georg; Šimić, Gordana; Magdić, Damir (2009)
Summary: Glutenin is a group of polymeric gluten proteins. Glutenin molecules consist of glutenin subunits linked together with disulphide bonds and having higher (HMM-GS) and lower (LMM-GS) molecular mass. The main objective of this study is the evaluation of the influence of HMM-GS on flour processing properties.
Congress of Croatian society of biochemistry and molecular biology, Osijek, Croatia, 17-20 September 2008
Bibliografija: 24 jed
Keywords: Glutenin -- Molekularna masa -- Analiza glavnih komponenata -- Pšenica